KREATIVITAS DAN IMAJINASI ANAK DENGAN BERMAIN PLAY BOARD - Eka Poppi Hutami; Pertiwi Kamariah Hasis; Ilma Latifathul Lutfiah (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2023)
This problem is that children's creative abilities and children's imagination have not developed according to expectations for the students at Bunda Pertiwi Palopo TPA. The aim of this improvement is expected to be to increase children's creativity and imagination by playing on the play board at Bunda Pertiwi Palopo TPA. The plan for each cycle refers to the Kemmis and Taggart action research model. How to collect data can be done by observing in the form of checklists, anecdotal notes and documentation. Data analysis techniques using quantitative data processing techniques. The results of action in cycle 1 averaged 11.50 or 48% showing children who had not yet appeared. The average results of the second cycle of action reached 19.75 or 82%, indicating that children were starting to develop. very good totaling 60 children, in play board activities the children developed very well with 60%, they did it independently and were able to help their friends who had not yet achieved the expected creative abilities. From cycle 1 to cycle 2 there was an increase of 5.67 or 28 percentages.